PREGNANCY IN OBESE WOMEN: OBSTETRIC AND PERINATAL OUTCOMES - Игитова, Марина Борисовна; Долгова, Надежда Сергеевна; Яворская, Светлана Дмитриевна; Дмитриенко, Ксения Владимировна; Кравцова, Елена Станиславовна (Mother and Baby in Kuzbass, 2025)
The aim of the reseach – to assess the obstetric and perinatal outcomes structure and frequency obstetric and perinatal outcomes among obese pregnant women. Materials and methods. First (retrospective) stage: 150 birth histories were selected, 52 patients with obesity (group I) and 98 pregnant women with normal body mass index (group II). Second (prospective cohort) stage is case-control study has contained blood serum C-reactive protein determinationin 20 women with obesity and in 30 with normal body mass index. Statistical data processing was performed using MedCalc Version 18.2.1 software (license Z2367-F3DD4-83E2E8-A6963-ED902) using nonparametric statistics methods. Results. In group I patients were significantly older than in group II (30.5 [27.5-34.5] and 27 [25.0-32.0]; p = 0.0001). Somatic diseases were hypertensive syndrome (40.3% and 6.3%; p < 0,001) and urinary system infectious diseases (27.8% and 15.6%; p = 0.04) were found more often. Among obese patients, there was a high proportion of multiparous women (75% and 36.7%; p = 0.001), with a history of miscarriage (70.8% and 50%; p = 0.007), infertility (8.3% and 1.6%; p = 0.05) and those who had orerative abdoninal delivery (41.6% and 15.6%; p = 0.001). In Group I pregancy complicatioma were gestational arterial hypertension (22.2% and 7.8%; p = 0.008), preeclampsia (22.2% and 5.4%; p = 0.001), gestational diabetes (29.2% and 9.4%; p = 0.0006), intrauterine growth restriction (6.9% and 0.8%; p = 0.004), perinatal hypoxia (38.9% and 17.9%; p = 0.003). C-reactive protein concentration in patients I group was significantly higher and steadily increased, reaching the maximum level in the third trimester. Newborns of obese mothers more often had large or small body weight for the gestational age and were more often transferred to the second nursing stage. Conclusion. Pregnancy in obese patients is associated with a higher incidence of obstetric and perital complications.